Dye detoxification by Lentinula edodes INCQS 40220 - Ludmila R. Bergsten-Torralba; Helena P.S. Zamith; Taline Ramos Conde; Claudia A.F. Aiub; Israel Felzenszwalb; Manuela da Silva (Fundação Oswaldo Cruz (FIOCRUZ), 2016)
Lentinula edodes belongs to the group of fungi known as ligninolytic fungi, due to its ability to degrade the aromatic structure of the lignin. Textile dyes also have aromatic structure, and after microbial degradation, some of them can be transformed into toxic compounds, when compared to the original structure, representing risk to environment and human health. Therefore, the potential of the fungus L. edodes INCQS 40220 to decolorize and to detoxify reactive red 198 (azo dye), reactive blue 214 (azo dye) and reactive blue 21 (cooper phthalocyanine dye) in a mixture (MXD), was evaluated. After 14 days of incubation, total decolorization in liquid media was obtained. The fungal treatment of MXD did not present toxic effects towards blood human cells. The genotoxicity of MXD, assessed by Comet assay, was efficiently reduced to 61% and in the Ames test presented negative response for mutagenicity for Salmonella enterica serovar Typhimurium TA97, TA98, TA100 and TA102 strains. The results indicated L. edodes INCQS 40220 efficiency on decolorization and genotoxicity reduction of a mixture of different dyes. Therefore, based on these results, obtained under laboratory conditions, L. edodes INCQS 40220 has potential for textile effluent treatment.